Phylogenetic Relatedness Among Plasmids Harbored by Campylobacter jejuni and Campylobacter coli Isolated From Retail Meats - Marasini, Daya; Karki, Anand B.; Buchheim, Mark A.; Fakhr, Mohamed K. (Frontiers in Microbiology, 2018)
Campylobacter jejuni and Campylobacter coli are two of the major causes of foodborne illness. In this study, 29 plasmids isolated from 20 retail meat isolates of Campylobacter jejuni and Campylobacter coli were fully-sequenced individually or as a part of a whole genome sequencing approach. The fully-sequenced plasmids ranged in size from 3 kb to 119 kb. Molecular characterization of the sequenced plasmids was based on pangenomic analysis and types of genes present on these plasmids and similar ones from Genbank. The plasmids were categorized into four different groups. These groups include type-1 that consisted mainly of pTet plasmids with the tetO gene, type-2 plasmids commonly found in C. coli strains, type-3 which have pVir plasmids, and type-4 that consisted mainly of smaller plasmids. The type-2 plasmids were unique, common among C. coli strains, and carried several conjugative transfer genes. The type-2 plasmids were most similar to a plasmid from Helicobacter pullorum. Maximum parsimony analysis and NeighborNet analysis were used to assess the phylogenetic relatedness among the 29 plasmid sequences presented in this study in addition to the other 104 plasmid sequences of Campylobacter species available in GenBank to date. Results from MP analysis revealed multiple lineages among Campylobacter plasmids which was supported by NeighborNet analysis. Clustering of plasmids did not conform to species-specific clades which suggested an intra-species dissemination of plasmids among Campylobacter species. To our knowledge, this is the first extensive phylogenetic analysis of Campylobacter plasmids sequenced to date.